Education Paradigm Reform for Quality and Equitable Learning: A Qualitative Analysis - Amir, Abdul Rozak (UIN Sunan Gunung Djati Bandung, 2023)
Reforming the educational paradigm towards equitable and quality education is an imperative endeavor to establish a more effective and inclusive education system. This research adopts a qualitative approach, employing library research as the primary data collection technique. The sources utilized in this study encompass books, scientific journals, literature, and pertinent publications. The findings reveal a comprehensive reform agenda, encompassing inclusivity and accessibility, enhancements in learning quality, the implementation of competency-based education, resource provision and capacity building, as well as active engagement with the community and stakeholders. By embracing this educational paradigm reform, the aspiration is to foster a more equitable educational landscape, providing equal opportunities for all individuals, devoid of any form of discrimination